Law and Government in England during the Long Eighteenth Century - Lemmings, D. author. aut Link
X, 269 p.
Keywords: Over the long eighteenth century English governance was transformed by large adjustments to the legal instruments and processes of power. This book documents and analyzes these shifts and focuses upon the changing relations between legal authority and the English people.